2003
DOI: 10.1093/ajcn/77.6.1417
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and changes in body mass index and waist circumference in adults

Abstract: Consuming a diet high in fruit, vegetables, reduced-fat dairy, and whole grains and low in red and processed meat, fast food, and soda was associated with smaller gains in BMI and waist circumference. Because foods are not consumed in isolation, dietary pattern research based on natural eating behavior may be useful in understanding dietary causes of obesity and in helping individuals trying to control their weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

35
312
5
25

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 453 publications
(377 citation statements)
references
References 56 publications
35
312
5
25
Order By: Relevance
“…The patterns we find in this study are similar to patterns found in several other studies. The Western pattern (Slattery et al, 1998;Fung et al, 2001;Terry et al, 2001) and the healthy pattern (or 'prudent pattern') are reported by many others (Slattery et al, 1998;Fung et al, 2001;Pryer et al, 2001;Terry et al, 2001;Chen et al, 2002;Newby et al, 2003), the same is the case for the alcohol pattern (Slattery et al, 1998;Terry et al, 2001;Newby et al, 2003) and the average pattern (or LER pattern) (Fraser et al, 2000;Greenwood et al, 2000;Millen et al, 2002). Several studies also report traditional diet patterns (Greenwood et al, 2000;Pryer et al, 2001;van Dam et al, 2003), but these are naturally different from the ones we find in our study since traditional patterns are specific to each country.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The patterns we find in this study are similar to patterns found in several other studies. The Western pattern (Slattery et al, 1998;Fung et al, 2001;Terry et al, 2001) and the healthy pattern (or 'prudent pattern') are reported by many others (Slattery et al, 1998;Fung et al, 2001;Pryer et al, 2001;Terry et al, 2001;Chen et al, 2002;Newby et al, 2003), the same is the case for the alcohol pattern (Slattery et al, 1998;Terry et al, 2001;Newby et al, 2003) and the average pattern (or LER pattern) (Fraser et al, 2000;Greenwood et al, 2000;Millen et al, 2002). Several studies also report traditional diet patterns (Greenwood et al, 2000;Pryer et al, 2001;van Dam et al, 2003), but these are naturally different from the ones we find in our study since traditional patterns are specific to each country.…”
Section: Discussionsupporting
confidence: 51%
“…Both Slattery et al (1998) and Newby et al (2003) found highest percentage of current smokers among their alcohol patterns. As in our study, Slattery et al (1998) found that persons in the alcohol pattern were more likely to have higher income, but in contrast to what we found Slattery also found that they were more likely to have higher education.…”
Section: Discussionmentioning
confidence: 92%
“…16 As, only few longitudinal studies have been performed to examine the link between dietary patterns and BMI or obesity. [17][18][19][20][21][22] Among them, one study found that food factors could not consistently predict changes in BMI or obesity development, 22 whereas the others showed that dietary patterns were significantly related to changes in BMI over time. [17][18][19]21 According to these studies, it seems that the adoption of a dietary pattern characterized by high intakes of red and processed meats, refined grains, sweets and desserts is associated with larger weight gain, whereas a dietary pattern usually characterized by high intakes of fruits, vegetables, whole grains, fish and poultry may facilitate weight maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have considered the role of dietary patterns in the development of central obesity among adults (18)(19)(20)(21) , data related to the role of food group intake in the development of central obesity at younger ages is very limited. The US Department of Agriculture's (USDA) Food Guide Pyramid and Dietary Guidelines for Americans (issued every five years) provide food-based intake guidelines for children and adults (22) .…”
mentioning
confidence: 99%